Effect of integrative neuromuscular training for injury prevention and sports performance of female badminton players - Zhao, W.; Wang, C.; Bi, Y.; Chen, L. (BioMed Research International, 2021)
Objectives. Investigate the effects of integrated neuromuscular training (INT) on injury prevention and the performance ofprofessional female badminton athletes by comparing their preintervention and postintervention tests. The study hypothesizedthat integrated neuromuscular training can improve the asymmetry and improve the sport performance of female badminton players. Methods. According to pretest value based on functional movement screening, 38 participants were divided into a high-risk group (HG) and a low-risk group (LG) with 22 and 16 people in each group. Two groups of athletes took part in an 8-week INT program consisting of four 90-min sessions each week. The asymmetries in movement, physical fitness, and special abilities were tested before and after the intervention. Independent samplet-test was used for the statistical analysis. Results. This research found indicated that 8 weeks of INT influenced FMS scores in both groups (HG and LG). The change of inline lunge (ESH=0:42,ESL=0:21) and trunk stability push-up (ESH=-0:58, ESL=-0:20) showed significant differences (P<0:05), and the change of the FMS scores (ESH=0:81, ESL=0:65), deep squat (ESH=0:6, ESL=0:3), and rotation stability (ESH=-0:65, ESL=-0:72) showed very significant differences (P<0:01). Compared to the pretest, most of the physicalfitness parametersimproved significantly in the HG and LG groups except strength index, and special abilities of the HG and LG group womenbadminton athletes showed a substantial increase. Conclusion. Integrated neuromuscular training can effectively improve the asymmetry of female badminton athletes`limbs, prevent sports injury, and improve the athlete`s performance ability. However,athletes in different risk groups have certain differences in the degree of improvement in their motor skills.